2017
DOI: 10.1007/s11695-017-2593-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Physical Activity After Gastric Bypass—a Prospective Study

Abstract: Despite large differences between accelerometer-based and subjective estimates of physical activity, the associations of self-regulatory factors and weight loss with postoperative physical activity did not vary depending on mode of measurement. Self-regulation predicted both objective and self-reported physical activity. Targeting patients' self-regulatory ability may enhance physical activity after gastric bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
(43 reference statements)
3
13
0
Order By: Relevance
“…Previous studies, using self-reported questionnaires, have shown that bariatric surgery patients increase, often with over 20%, their time spent in MVPA post-surgery [9]. In contrast, when bariatric patients have worn objective physical activity measures, such as accelerometers, the results show that overall physical activity and MVPA do not increase [19][20][21][22][23][24][25], or increase to a small extent after surgery [26]. Only a few studies have evaluated the discrepancies between self-reported and accelerometer-measured physical activity pre-to postsurgery within the same individuals [19,23,27].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies, using self-reported questionnaires, have shown that bariatric surgery patients increase, often with over 20%, their time spent in MVPA post-surgery [9]. In contrast, when bariatric patients have worn objective physical activity measures, such as accelerometers, the results show that overall physical activity and MVPA do not increase [19][20][21][22][23][24][25], or increase to a small extent after surgery [26]. Only a few studies have evaluated the discrepancies between self-reported and accelerometer-measured physical activity pre-to postsurgery within the same individuals [19,23,27].…”
Section: Introductionmentioning
confidence: 74%
“…A study by Bergh et al showed a high prevalence of overestimating the time spent in MVPA, assessed by selfadministered questionnaire, compared with objective- measured MVPA up to 24 months post-surgery, but, no objective data at pre-surgery were available to be able to compare the difference from pre-to post-surgery. However, their results showed a high over-reporting of time spent in MVPA, where 80% of the participants reported to have met the weekly MVPA guidelines, while according to objective measures the prevalence was only 17.9% [24]. People with obesity tend to overestimate their MVPA levels [28,35] and also misclassify the intensity of physical activity to a higher extent than people of normal weight [35].…”
Section: Previous Researchmentioning
confidence: 95%
“…In recent years, few studies have shed light on the factors influencing PA participation in bariatric patients. For instance, Bergh, Kvalem, Mala, Hansen, and Sniehotta (2017) showed that being single, higher education level, and greater self-regulation predicted PA. Reid et al (2016) indicated that neighbourhood walkability did not influence either daily steps or sedentary time. From a qualitative perspective, Wiklund, Fagevik, Olbers, and Willén (2014) pointed out that some physical side effects of bariatric surgery, such as diarrhoea or excess skin, prevented patients from being as active as they would like to be.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bariatric patients are advised to engage in regular physical activity [8][9][10][11]. Previous studies indicate that low physical activity after bariatric surgery is related to less weight loss and more weight regain [12][13][14], though more recent studies question whether weight loss is positively influenced by adherence to a healthy lifestyle with regular physical activity [15,16].…”
Section: Introductionmentioning
confidence: 99%